Challenges and Opportunities for Strengthening Bottom‐Tow Fisheries Sustainability - Suresh A. Sethi; Robert D. Murphy; Matthew R. Baker; Anita C. Kroska; Haraldur A. Einarsson; Owen S. Hamel; Shelton J. Harley; Pingguo He; James Ianelli; Stan Kotwicki; Robert A. McConnaughey; Chris McGonigle; et al. (Fish and Fisheries, 2026)
Bottom‐tow gear fisheries (trawls and dredges) produce ~24 million mt of harvest annually, representing a globally important animal‐sourced food system. While many are currently sustainably managed, growing concern over the potential for ecosystem impacts from bottom‐tow gears has increased pressure to improve these fisheries. We assembled an international working group of > 30 contributors, including fishing industry participants, managers, non‐governmental ocean conservation organization representatives, and scientists to synthesize obstacles to bottom‐tow fisheries sustainability and to develop expert‐based recommendations to operationalize sustainability advancements moving forward. We identified 30 key gaps impeding bottom‐towed fisheries sustainability spanning 6 core challenge areas including: seafloor disturbance, bycatch and discards, management design and implementation, fishing operations, cross‐sector conflicts, and public perception and communication. We generated 28 priority recommendations to address bottom‐tow fisheries sustainability obstacles with themes including: addressing data gaps, advancing mechanistic understanding and modelling tools, strengthening management processes, and improving knowledge sharing and communication. Cross‐disciplinary and diverse system experience among fisheries and marine ecosystem stakeholders will be critical for operationalizing bottom‐tow fisheries sustainability advancements. As the global human population approaches 10 bn in the next 30 years, ensuring sustainable wild capture fisheries is an imperative for feeding the world. Outputs from this synthesis serve as a resource for fishing and marine ecosystem stakeholders to identify key challenge areas and associated entry points for solutions‐oriented efforts to improve the sustainability of bottom‐tow fisheries.

Machine learning derived abdominal aortic calcification is associated with physical frailty in community-dwelling adults: the UK Biobank Imaging Study - Abadi K. Gebre; Marion Mundt; Elsa Dent; James Webster; Afsah Saleem; Syed Zulqarnain Gilani; Yuandan Zhang; Cassandra Smith; Parminder Raina; John P. Kemp; William D. Leslie; John T. Schousboe; et al. (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Correction to: The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2026)

The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

First report of carnation Italian ringspot virus in Gypsophila in the United Kingdom - G. Webster; L. Frew; R. Ward; A. R. Fowkes; A. Skelton; V. Harju; I. P. Adams; S. McGreig; H. Pufal; C. Conyers; A. Fox (Journal of Plant Pathology, 2024)

Protecting the invisible: Establishing guideline values for copper toxicity to marine microbiomes - Marie C. Thomas; Gretel Waugh; Inka Vanwonterghem; Nicole S. Webster; Christian Rinke; Rebecca Fisher; Heidi M. Luter; Andrew P. Negri (Science of The Total Environment, 2023)

Low‐coverage whole genome sequencing for highly accurate population assignment: Mapping migratory connectivity in the American Redstart ( Setophaga ruticilla ) - Matthew G. DeSaix; Eric C. Anderson; Christen M. Bossu; Christine E. Rayne; Teia M. Schweizer; Nicholas J. Bayly; Darshan S. Narang; Julie C. Hagelin; H. Lisle Gibbs; James F. Saracco; Thomas W. Sherry; Michael S. Webster; et al. (Molecular Ecology, 2023)
Understanding the geographic linkages among populations across the annual cycle is an essential component for understanding the ecology and evolution of migratory species and for facilitating their effective conservation. While genetic markers have been widely applied to describe migratory connections, the rapid development of new sequencing methods, such as low‐coverage whole genome sequencing (lcWGS), provides new opportunities for improved estimates of migratory connectivity. Here, we use lcWGS to identify fine‐scale population structure in a widespread songbird, the American Redstart ( Setophaga ruticilla ), and accurately assign individuals to genetically distinct breeding populations. Assignment of individuals from the nonbreeding range reveals population‐specific patterns of varying migratory connectivity. By combining migratory connectivity results with demographic analysis of population abundance and trends, we consider full annual cycle conservation strategies for preserving numbers of individuals and genetic diversity. Notably, we highlight the importance of the Northern Temperate‐Greater Antilles migratory population as containing the largest proportion of individuals in the species. Finally, we highlight valuable considerations for other population assignment studies aimed at using lcWGS. Our results have broad implications for improving our understanding of the ecology and evolution of migratory species through conservation genomics approaches.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Genomic analysis of a parasite invasion: Colonization of the Americas by the blood fluke Schistosoma mansoni - Roy N. Platt; Winka Le Clec'h; Frédéric D. Chevalier; Marina McDew‐White; Philip T. LoVerde; Rafael Ramiro de Assis; Guilherme Oliveira; Safari Kinung'hi; Amadou Garba Djirmay; Michelle L. Steinauer; Anouk Gouvras; Muriel Rabone; et al. (Molecular Ecology, 2022)
Schistosoma mansoni , a snail‐borne, blood fluke that infects humans, was introduced into the Americas from Africa during the Trans‐Atlantic slave trade. As this parasite shows strong specificity to the snail intermediate host, we expected that adaptation to South American Biomphalaria spp. snails would result in population bottlenecks and strong signatures of selection. We scored 475,081 single nucleotide variants in 143 S. mansoni from the Americas (Brazil, Guadeloupe and Puerto Rico) and Africa (Cameroon, Niger, Senegal, Tanzania, and Uganda), and used these data to ask: (i) Was there a population bottleneck during colonization? (ii) Can we identify signatures of selection associated with colonization? (iii) What were the source populations for colonizing parasites? We found a 2.4‐ to 2.9‐fold reduction in diversity and much slower decay in linkage disequilibrium (LD) in parasites from East to West Africa. However, we observed similar nuclear diversity and LD in West Africa and Brazil, suggesting no strong bottlenecks and limited barriers to colonization. We identified five genome regions showing selection in the Americas, compared with three in West Africa and none in East Africa, which we speculate may reflect adaptation during colonization. Finally, we infer that unsampled populations from central African regions between Benin and Angola, with contributions from Niger, are probably the major source(s) for Brazilian S. mansoni . The absence of a bottleneck suggests that this is a rare case of a serendipitous invasion, where S. mansoni parasites were pre‐adapted to the Americas and able to establish with relative ease.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Morphology and sedimentology of the shelf-upper slope transition in the Abrolhos continental shelf (east Brazilian margin) - Danielle P. D’Agostini; Alex C. Bastos; Gilberto M. Amado-Filho; Claudia G. Vilela; Thaís C. S. Oliveira; Jody M. Webster; Rodrigo L. Moura (Geo-Marine Letters, 2019)

Sedimentology, structure and age estimate of five continental slope submarine landslides, eastern Australia - S. Clarke; T. Hubble; J. Webster; D. Airey; E. De Carli; C. Ferraz; P. Reimer; R. Boyd; J. Keene (Australian Journal of Earth Sciences, 2016)

CMV in the gut: a critical review of CMV detection in the immunocompetent host with colitis - A. L. Goodman; C. D. Murray; J. Watkins; P. D. Griffiths; D. P. Webster (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

You are not always what we think you eat: selective assimilation across multiple whole‐stream isotopic tracer studies - W. K. Dodds; S. M. Collins; S. K. Hamilton; J. L. Tank; S. Johnson; J. R. Webster; K. S. Simon; M. R. Whiles; H. M. Rantala; W. H. McDowell; S. D. Peterson; T. Riis; et al. (Ecology, 2014)
Analyses of 21 15 N stable isotope tracer experiments, designed to examine food web dynamics in streams around the world, indicated that the isotopic composition of food resources assimilated by primary consumers (mostly invertebrates) poorly reflected the presumed food sources. Modeling indicated that consumers assimilated only 33–50% of the N available in sampled food sources such as decomposing leaves, epilithon, and fine particulate detritus over feeding periods of weeks or more. Thus, common methods of sampling food sources consumed by animals in streams do not sufficiently reflect the pool of N they assimilate. Isotope tracer studies, combined with modeling and food separation techniques, can improve estimation of N pools in food sources that are assimilated by consumers. Food web studies that use putative food samples composed of actively cycling (more readily assimilable) and refractory (less assimilable) N fractions may draw erroneous conclusions about diets, N turnover, and trophic linkages of consumers. By extension, food web studies using stoichiometric or natural abundance approaches that rely on an accurate description of food‐source composition could result in errors when an actively cycling pool that is only a fraction of the N pool in sampled food resources is not accounted for.

Genotypic variation in the ability of wheat roots to penetrate wax layers - W. R. Whalley; I. C. Dodd; C. W. Watts; C. P. Webster; A. L. Phillips; J. Andralojc; R. P. White; W. J. Davies; M. A. J. Parry (Plant and Soil, 2013)

Sodium bicarbonate supplementation improves hypertrophy-type resistance exercise performance - Benjamin M. Carr; Michael J. Webster; Joseph C. Boyd; Geoffrey M. Hudson; Timothy P. Scheett (European Journal of Applied Physiology, 2013)

Diversity of Scleractinia and Octocorallia in the mesophotic zone of the Great Barrier Reef, Australia - T. C. L. Bridge; K. E. Fabricius; P. Bongaerts; C. C. Wallace; P. R. Muir; T. J. Done; J. M. Webster (Coral Reefs, 2012)

Enrichment culture of CSF is of limited value in the diagnosis of neonatal meningitis - S. H. Chaudhry; D. Wagstaff; A. Gupta; I. C. Bowler; D. P. Webster (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Application of a serial extended forecast experiment using the ECMWF model to interpret the predictive skill of tropical intraseasonal variability - P. A. Agudelo; C. D. Hoyos; P. J. Webster; J. A. Curry (Climate Dynamics, 2009)

Nitrate removal in stream ecosystems measured by 15N addition experiments: Total uptake - Robert O. Hall; Jennifer L. Tank; Daniel J. Sobota; Patrick J. Mulholland; Jonathan M. O'Brien; Walter K. Dodds; Jackson R. Webster; H. Maurice Valett; Geoffrey C. Poole; Bruce J. Peterson; Judy L. Meyer; William H. McDowell; et al. (Limnology and Oceanography, 2009)
We measured uptake length of 15 NO 3 − in 72 streams in eight regions across the United States and Puerto Rico to develop quantitative predictive models on controls of NO 3 − uptake length. As part of the Lotic Intersite Nitrogen eXperiment II project, we chose nine streams in each region corresponding to natural (reference), suburban‐urban, and agricultural land uses. Study streams spanned a range of human land use to maximize variation in NO 3 − concentration, geomorphology, and metabolism. We tested a causal model predicting controls on NO 3 − uptake length using structural equation modeling. The model included concomitant measurements of ecosystem metabolism, hydraulic parameters, and nitrogen concentration. We compared this structural equation model to multiple regression models which included additional biotic, catchment, and riparian variables. The structural equation model explained 79% of the variation in log uptake length ( S Wtot ). Uptake length increased with specific discharge ( Q/w ) and increasing NO 3 − concentrations, showing a loss in removal efficiency in streams with high NO 3 − concentration. Uptake lengths shortened with increasing gross primary production, suggesting autotrophic assimilation dominated NO 3 − removal. The fraction of catchment area as agriculture and suburban‐urban land use weakly predicted NO 3 − uptake in bivariate regression, and did improve prediction in a set of multiple regression models. Adding land use to the structural equation model showed that land use indirectly affected NO 3 − uptake lengths via directly increasing both gross primary production and NO 3 − concentration. Gross primary production shortened S Wtot , while increasing NO 3 − lengthened S Wtot resulting in no net effect of land use on NO 3 − removal.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

ENDOGENOUS AND EXOGENOUS CONTROL OF ECOSYSTEM FUNCTION: N CYCLING IN HEADWATER STREAMS - H. M. Valett; S. A. Thomas; P. J. Mulholland; J. R. Webster; C. N. Dahm; C. S. Fellows; C. L. Crenshaw; C. G. Peterson (Ecology, 2008)
Allochthonous inputs act as resource subsidies to many ecosystems, where they exert strong influences on metabolism and material cycling. At the same time, metabolic theory proposes endogenous thermal control independent of resource supply. To address the relative importance of exogenous and endogenous influences, we quantified spatial and temporal variation in ecosystem metabolism and nitrogen (N) uptake using seasonal releases of 15 N as nitrate in six streams differing in riparian–stream interaction and metabolic character. Nitrate removal was quantified using a nutrient spiraling approach based on measurements of downstream decline in 15 N flux. Respiration ( R ) and gross primary production (GPP) were measured with whole‐stream diel oxygen budgets. Uptake and metabolism metrics were addressed as z scores relative to site means to assess temporal variation. In open‐canopied streams, areal uptake ( U ; μg N·m −2 ·s −1 ) was closely related to GPP, metabolic rates increased with temperature, and R was accurately predicted by metabolic scaling relationships. In forested streams, N spiraling was not related to GPP; instead, uptake velocity ( v f ; mm/s) was closely related to R . In contrast to open‐canopied streams, N uptake and metabolic activity were negatively correlated to temperature and poorly described by scaling laws. We contend that streams differ along a gradient of exogenous and endogenous control that relates to the relative influences of resource subsidies and in‐stream energetics as determinants of seasonal patterns of metabolism and N cycling. Our research suggests that temporal variation in the propagation of ecological influence between adjacent systems generates phases when ecosystems are alternatively characterized as endogenously and exogenously controlled.

Modelling adaptive management strategies for coping with the impacts of climate variability and change on riverine algal blooms - NEIL R. VINEY; BRYSON C. BATES; STEPHEN P. CHARLES; IAN T. WEBSTER; MYRIAM BORMANS (Global Change Biology, 2007)
The impact of climate change on hydrology and water resources is one of the most critical issues facing the world in the next few decades. In particular, there is a need to quantify the risks associated with maintaining the security of resource quantity and quality, and to assess the effectiveness of potential management strategies. In this paper, we assess the impacts of climate variability and change on one aspect of river health. A simple model of Anabaena algal bloom occurrence at a weir pool in the lower Murrumbidgee River, Australia, has been coupled to a catchment model that is used to simulate streamflow, irrigation demand and diversions, dam water storage and releases, and decision‐making by both irrigators and managers. Long‐term climate data are obtained from a statistical downscaling algorithm, which, when applied to global climate model predictions can provide climate data suitable for driving the coupled model under a variety of climatic scenarios. The coupled model is then used to assess the impact of climate variability and projected climate change on the frequency, duration and magnitude of Anabaena blooms. The impact of two management strategies for bloom control are also assessed and it is shown that even a single, quite simple, resource‐neutral, adaptive management strategy has the potential to substantially reduce the occurrence and impact of algal blooms and to more than compensate for the deleterious impacts of climate change. This result supports the notion that planning for the future can lead to positive outcomes in the present.

A comparison of stable‐isotope probing of DNA and phospholipid fatty acids to study prokaryotic functional diversity in sulfate‐reducing marine sediment enrichment slurries - Gordon Webster; Lynsey C. Watt; Joachim Rinna; John C. Fry; Richard P. Evershed; R. John Parkes; Andrew J. Weightman (Environmental Microbiology, 2006)
Summary Marine sediment slurries enriched for anaerobic, sulfate‐reducing prokaryotic communities utilizing glucose and acetate were used to provide the first comparison between stable‐isotope probing (SIP) of phospholipid fatty acids (PLFA) and DNA (16S rRNA and dsrA genes) biomarkers. Different 13 C‐labelled substrates (glucose, acetate and pyruvate) at low concentrations (100 µM) were used over a 7‐day incubation to follow and identify carbon flow into different members of the community. Limited changes in total PLFA and bacterial 16S rRNA gene DGGE profiles over 7 days suggested the presence of a stable bacterial community. A broad range of PLFA were rapidly labelled (within 12 h) in the 13 C‐glucose slurry but this changed with time, suggesting the presence of an active glucose‐utilizing population and later development of another population able to utilize glucose metabolites. The identity of the major glucose‐utilizers was unclear as 13 C‐enriched PLFA were common (16:0, 16:1, 18:1ω7, highest incorporation) and there was little difference between 12 C‐ and 13 C‐DNA 16S rRNA gene denaturing gradient gel electrophoresis (DGGE) profiles. Seemingly glucose, a readily utilizable substrate, resulted in widespread incorporation consistent with the higher extent of 13 C‐incorporation (∼10 times) into PLFA compared with 13 C‐acetate or 13 C‐pyruvate. 13 C‐PLFA in the 13 C‐acetate and 13 C‐pyruvate slurries were similar to each other and to those that developed in the 13 C‐glucose slurry after 4 days. These were more diagnostic, with branched odd‐chain fatty acids ( i 15:0, a 15:0 and 15:1ω6) possibly indicating the presence of Desulfococcus or Desulfosarcina sulfate‐reducing bacteria (SRB) and sequences related to these SRB were in the 13 C‐acetate‐DNA dsrA gene library. The 13 C‐acetate‐DNA 16S rRNA gene library also contained sequences closely related to SRB, but these were the acetate‐utilizing Desulfobacter sp., as well as a broad range of uncultured Bacteria. In contrast, analysis of DGGE bands from 13 C‐DNA demonstrated that the candidate division JS1 and Firmicutes were actively assimilating 13 C‐acetate. Denaturing gradient gel electrophoresis also confirmed the presence of JS1 in the 13 C‐DNA from the 13 C‐glucose slurry. These results demonstrate that JS1, originally found in deep subsurface sediments, is more widely distributed in marine sediments and provides the first indication of its metabolism; incorporation of acetate and glucose (or glucose metabolites) under anaerobic, sulfate‐reducing conditions. Here we demonstrate that PLFA‐ and DNA‐SIP can be used together in a sedimentary system, with low concentrations of 13 C‐substrate and overlapping incubation times (up to 7 days) to provide complementary, although not identical, information on carbon flow and the identity of active members of an anaerobic prokaryotic community.

Phylogeography of Biomphalaria glabrata and B. pfeifferi , important intermediate hosts of Schistosoma mansoni in the New and Old World tropics - R. J. Dejong; J. A. T. Morgan; W. D. Wilson; M. H. Al‐Jaser; C. C. Appleton; G. Coulibaly; P. S. D’Andrea; M. J. Doenhoff; W. Haas; M. A. Idris; L. A. Magalhães; H. Moné; et al. (Molecular Ecology, 2003)
The historical phylogeography of the two most important intermediate host species of the human blood fluke Schistosoma mansoni , B. glabrata in the New World, and B. pfeifferi in the Old World, was investigated using partial 16S and ND1 sequences from the mitochondrial genome. Nuclear sequences of an actin intron and internal transcribed spacer (ITS)‐1 were also obtained, but they were uninformative for the relationships among populations. Phylogenetic analyses based on mtDNA revealed six well‐differentiated clades within B. glabrata : the Greater Antilles, Venezuela and the Lesser Antilles, and four geographically overlapping Brazilian clades. Application of a Biomphalaria ‐specific mutation rate gives an estimate of the early Pleistocene for their divergence. The Brazilian clades were inferred to be the result of fragmentation, due possibly to climate oscillations, with subsequent range expansion producing the overlapping ranges. Within the Venezuela and Lesser Antilles clade, lineages from each of these areas were estimated to have separated approximately 740 000 years ago. Compared to B. glabrata , mitochondrial sequences of B. pfeifferi are about 4× lower in diversity, reflecting a much younger age for the species, with the most recent common ancestor of all haplotypes estimated to have existed 880 000 years ago. The oldest B . pfeifferi haplotypes occurred in southern Africa, suggesting it may have been a refugium during dry periods. A recent range expansion was inferred for eastern Africa less than 100 000 years ago. Several putative species and subspecies, B. arabica, B. gaudi, B. rhodesiensis and B. stanleyi , are shown to be undifferentiated from other B. pfeifferi populations.

Soluble organic nitrogen in agricultural soils - D. V. Murphy; A. J. Macdonald; E. A. Stockdale; K. W. T. Goulding; S. Fortune; J. L. Gaunt; P. R. Poulton; J. A. Wakefield; C. P. Webster; W. S. Wilmer (Biology and Fertility of Soils, 2000)

Relation between drug resistance and antigenicity among norakin-resistant mutants of influenza A (fowl plague) virus - A. I. Klimov; S. G. Markushin; S. Prsch; V. P. Ginzburg; H. Heider; A. M. Heider; C. Schreder; R. G. Webster (Archives of Virology, 1992)

Persistence of Q strain of H2N2 influenza virus in avian species: Antigenic, biological and genetic analysis of avian and human H2N2 viruses - K. Nerome; Y. Yoshioka; C. A. Torres; A. Oya; P. Bachmann; K. Ottis; R. G. Webster (Archives of Virology, 1984)